2010
DOI: 10.1021/ja101556g
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization and Rearrangement Reactions of an Fragment Ions of Protonated Peptides

Abstract: a(n) ions are frequently formed in collision-induced dissociation (CID) of protonated peptides in tandem mass spectrometry (MS/MS) based sequencing experiments. These ions have generally been assumed to exist as immonium derivatives (-HN(+)═CHR). Using a quadrupole ion trap mass spectrometer, MS/MS experiments have been performed and the structure of a(n) ions formed from oligoglycines was probed by infrared spectroscopy. The structure and isomerization reactions of the same ions were studied using density fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
124
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(137 citation statements)
references
References 58 publications
12
124
0
1
Order By: Relevance
“…Initially, it was believed [10,35,43] that the a 2 ion was a substituted imine ion shown as Breakdown graph for the Tyr-Gly b 2 ion derived from Tyr-Gly-Gly a 2 in Scheme 1. However, the computational studies [31][32][33] as well as IRMPD studies [44][45][46] have shown that the cyclic structure is more stable and can be readily formed (Scheme 1). It should be noted that the calculations show [31][32][33] that the transition state for loss of CO is considerably higher than the energies of either a 2 or a 1 products.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Initially, it was believed [10,35,43] that the a 2 ion was a substituted imine ion shown as Breakdown graph for the Tyr-Gly b 2 ion derived from Tyr-Gly-Gly a 2 in Scheme 1. However, the computational studies [31][32][33] as well as IRMPD studies [44][45][46] have shown that the cyclic structure is more stable and can be readily formed (Scheme 1). It should be noted that the calculations show [31][32][33] that the transition state for loss of CO is considerably higher than the energies of either a 2 or a 1 products.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…The formation, structure, and reactivity of a n ions have received less attention [28]. a n Ions are formed [5,6,[29][30][31][32] mainly [33] from b n ions by elimination of CO.…”
Section: Introductionmentioning
confidence: 99%
“…The amide bond forms the fundamental linkage between monomeric amino acid residues in peptide polymers, and it is important to understand its gas-phase chemistry, which has so far been studied mainly through the decomposition reactions of protonated amides and peptides [27][28][29][30][31]. The mobile proton model [32][33][34][35][36][37] was proposed and applied to the flexible peptides and proteins besides the rigid molecules to describe the mobility of the proton across the protonated species.…”
mentioning
confidence: 99%